Downregulation of BmSTAT transcription factor promoted nucleopolyhedrovirus replication in Bombyx mori - Liang, Wenjuan; Zhou, Li; Dang, Zhuo; Wang, Shiyuan; Zhao, Ping; Xia, Qingyou; Lu, Zhongyan (Frontiers in Microbiology, 2024)
The Janus kinase/signal transducer and activator of transcription (JAK/STAT) signaling pathway plays a crucial role in the viral immune processes of organisms, with STAT being a key transcription factor downstream in this pathway. The STAT gene of Bombyx mori has two splicing forms, named BmSTAT-S and BmSTAT-L. This study compared the effects of the two splicing forms on Bombyx mori nucleopolyhedrovirus (BmNPV) infection through cell-level interference and further explored whether BmSTAT participates in the immune response to BmNPV infection via transgenic intervention at the individual level. Our research results indicated that BmNPV upregulates the expression of BmSTAT-S and BmSTAT-L in Bombyx mori BmE cells and larvae. Furthermore, BmE cells with interference of BmSTAT-S or BmSTAT-L displayed significantly higher expression levels of the viral gene GP41 and increased viral fluorescence compared to the control group after 48 hours of infection with BmNPV. Then, we constructed transgenic silkworms with genetic interference, and the results showed that both the transgenic silkworms with systemic interference and midgut-specific interference of the two splice forms of BmSTAT exhibited significantly reduced survival rates and increased viral replication numbers after infection with BmNPV. The above results indicated that the BmSTAT gene is involved in the immune response of Bombyx mori to BmNPV and these findings lay the foundation for further research on the mechanism of JAK/STAT signaling pathway involvement in BmNPV infection.